Incidence and Predictors of Unsuspected Recurrent Laryngeal Nerve Lymph Node Metastases After Neoadjuvant Chemoradiotherapy in Patients with Esophageal Squamous Cell Carcinoma - Li, Zhi-Gang; Zhang, Xiao-Bin; Wen, Yu-Wen; Liu, Yun-Hen; Chao, Yin-Kai (World journal of surgery, 2018)
Background Radical lymph node (LN) dissection along the recurrent laryngeal nerve (RLN) area carries a substantial morbidity rate, and its usefulness in neoadjuvant chemoradiotherapy (nCRT)-treated esophageal cancer patients remains unclear. Methods This study was conducted in two Asian thoracic surgery centers. Patients with esophageal squamous cell carcinoma (ESCC) who were judged to be ycN-RLN(−) after nCRT and received bilateral RLN LN dissection were eligible. The incidence of unsuspected RLN LN involvement was analyzed, and we used least absolute shrinkage and selection operator (LASSO) regression to identify its predictors. Results A total of 56 patients (53 males and 3 females; mean age: 55 years) were included. The upper mediastinum—including the bilateral RLN area—was covered by the radiation field in 48 (85.3%) patients. Although all of them were judged as ycN-RLN(−), unsuspected RLN LN involvement was identified on pathological examination in 11 (19.6%) subjects, being the only positive nodal station in seven. LASSO regression identified the pre-nCRT RLN LN(cN-RLN) status as the only independent predictor of ypN-RLN positivity; in contrast, neither the tumor location nor the radiation dose to the upper mediastinum were independently associated with ypN-RLN(+). RLN nodal dissection resulted in positive LN discovery rates of 30.8 and 10% in ycN-RLN(−) patients who had positive and negative cN-RLNs before nCRT, respectively. Consequently, 23.1 and 6.7% of patients in each subgroup would have been understaged in the absence of RLN nodal dissection. Conclusion Nearly one-fifth of ESCC patients who were judged to be ycN-RLN(−) unexpectedly had positive ypN-RLN. The pre-nCRT cN-RLN status plays a key role in the selection of patients that should undergo RLN LN dissection after nCRT.